INTELLIGENT PAY PARK - RASPI-BASED SMART PARKING MANAGEMENT SYSTEM (CAHIERS MAGELLANES-NS, 2024)
The need for effective parking management systems has increased because of urbanization and an increase in the number of automobiles. Conventional parking arrangements frequently lead to traffic jams, wasted time, and pollution of the environment. To solve these issues and improve the overall parking experience, this Project offers a Smart Parking Management System that is based on the Internet of Things (IoT).The suggested method makes use of Internet of Things technology to build an intelligent and dynamic parking management system. Parking spots with sensors, a centralized data processing unit, and an intuitive mobile application are essential elements. Real-time occupancy status monitoring is continuously monitored by sensors that are installed into each parking space.